Some considerations on obstetrical aspects in perinatal mortality - Ludmir G., A. (2015)
Perinatal mortality at the mother and child Hospital "San Bartolomé" located in Lima, Perú, during the year may 1967 to april 1968 is reported. The PN mortality rate was 29.8%. Highest PN mortality occurred amongst premature babies: 59.2%. Toxemia was the most important (40%) of the maternal causes of PN mortality. Prevention of prematurity and toxemia should then help to further reduce PN mortality.